Classdojo Interactive Media To Enhance Students' Conceptual Understanding In Mathematics - Dida Hartati , Dida Hartati; Nurdin Muhamad; Ani Siti Anisah (Universitas Garut, 2025)
This research aims to improve the mathematical concept understanding of first-grade students at SD GIS Prima Insani through the use of ClassDojo interactive media. Using a quantitative experimental method, the study involved 55 students divided into an experimental class (n=26) and a control class (n=29). Pretest results indicated that the initial abilities of both groups were equivalent (p = 0.527). However, after the intervention, the Mann-Whitney test revealed a significant difference in posttest scores with an Sig. 0.038 < 0.05 The result N-Gain score of 0.57 indicates a